(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This research aims to highlight the important and effective role played by accounting information systems in banking and its impact on the possibility of achieving competitive advantage. The collection, classification, analysis, and submission of information to its users is one of the most important objectives that Iraqi banking departments seek to achieve under the acceleration of knowledge. By providing a robust database that is an effective tool for banks to achieve the principle of competitive advantage, these departments seek to develop their accounting information systems efficiently and effectively by employing their IT outputs in planning, The decision of the National Islamic Bank of Iraq, as well as the design of a questionnaire consisting of 20 paragraphs specialized in accounting information systems and 40 questionnaires, were distributed on the sample of the study. The role of accounting information systems in Iraqi banks and their impact on the achievement of competitive advantage. These indicators were analyzed and tested by means of the tests of F, P-value and impact statement through the R2 parameter using ANOVA. The research concluded that there is a significant effect on the systems. The accounting research to achieve a competitive advantage on the basis of which the alternative hypothesis was accepted. The research also reached a number of recommendations, the most important of which is that the departments of Iraqi banks are interested in investing and developing their accounting information systems and employing their information outputs in making the best administrative and investment decisions.